دور المقاصد الشرعية والقواعد الفقهية في تطوير الفتوى في المسائل الفقهية المالية المستجدة المعاصرة : EFFECT MAQASID SHARIAH AND JURISPRUDENTIAL RULES IN THE DEVELOPMENT OF FATWAS IN CONTEMPORARY EMERGING FINANCIAL JURISPRUDENTIAL ISSUES - Mostafa, Imad (I-iECONS e-proceedings, 2023)
: إنّ الهدف الرئيس للدراسة بيان أثر استخدام المقاصد الشرعية والقواعد الفقهية والأصولية في الوصول للفتوى في المسائل المالية المستجدة المعاصرة، والمنهج المتّبع هو التحليلي الاستقرائي في النصوص الشرعية والمآلات في المقاصد الشرعية ،حيث إنّ هذا يحتاج تحليل علمي للوقوف على رؤية اسلامية أصولية في أثر المقاصد الشرعية والقواعد الفقهية والأصولية في تطوّر الفتوى في المسائل المالية المعاصرة ،حيث كان من النتائج لهذه الدراسة التوصل إلى نقاط محددة في تطوير وضوابط الفتوى بحيث يكون الاجتهاد للوصول إلى الفتوى بالحكم الشرعي وفق طريقة محددة ومنضبطة ومتطوّرة وتواكب المستجدات المعاصرة وتؤدي للوصول إلى الفتوى بالطريقة الصحيحة. The main objective of this study is to demonstrate the impact of using Islamic objectives, jurisprudential rules, and foundational principles in issuing fatwas related to contemporary financial issues. The methodology adopted is analytical and inductive, involving the examination of legal texts and their implications in the realm of Islamic objectives. This necessitates a scholarly analysis to uncover an authentic Islamic perspective on the influence of Islamic objectives, jurisprudential rules, and foundational principles in the development of fatwas concerning contemporary financial matters. The findings of this study reveal specific points for enhancing the development and guidelines for issuing fatwas, ensuring that scholarly effort leads to the issuance of religiously sound fatwas in a systematic, regulated, and evolving manner that keeps pace with contemporary developments, ultimately resulting in the correct issuance of fatwas.